2016
DOI: 10.4103/0253-7613.186201
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of antioxidant effect of Nerium indicum in anxious rats

Abstract: Aim:The aim of this study was to analyze the ethyl acetate extract of Nerium indicum (NIE) flower for its antioxidant effect in anxious Sprague–Dawley rats.Materials and Methods:Animals were divided into six groups (n = 6) and treated with 200 mg/kg and 400 mg/kg p.o. of NIE for 21 days to assess its preventive and curative effects. Anxiety was induced by isolating animals socially for 21 days. Elevated plus maze (EPM) and light and dark model were used for measuring anxiety in animals. Oxidative stress parame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…Methanol extract of N. indicum lowers are more potent anti-oxidant than leaves (Vinayagam and Sudha, 2011). Mohale et al (2016) reported the antioxidant activity of ethyl acetate extract of N. indicum lowers. According to them treatment with this extract caused signi icant increase in the endogenous antioxidants, superoxide dismutase (SOD), catalase (CAT), and reduced glutathione (GSH) in blood and brain of rats (Mohale et al, 2016).…”
Section: Anti-oxidant Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Methanol extract of N. indicum lowers are more potent anti-oxidant than leaves (Vinayagam and Sudha, 2011). Mohale et al (2016) reported the antioxidant activity of ethyl acetate extract of N. indicum lowers. According to them treatment with this extract caused signi icant increase in the endogenous antioxidants, superoxide dismutase (SOD), catalase (CAT), and reduced glutathione (GSH) in blood and brain of rats (Mohale et al, 2016).…”
Section: Anti-oxidant Propertiesmentioning
confidence: 99%
“…Mohale et al (2016) reported the antioxidant activity of ethyl acetate extract of N. indicum lowers. According to them treatment with this extract caused signi icant increase in the endogenous antioxidants, superoxide dismutase (SOD), catalase (CAT), and reduced glutathione (GSH) in blood and brain of rats (Mohale et al, 2016). Several plant based products contain tremendous ROS scavenging capacity (Dey and Chaudhari, 2014).…”
Section: Anti-oxidant Propertiesmentioning
confidence: 99%
“…Psychiatric disorders like anxiety or depression were also proved to be connected with neurodegenerative disturbances as well as changes of immunological and oxidative parameters which were alleviated by plant extracts [ 111 , 112 ].…”
Section: The Protective Properties Of Plant Preparations Against Tmentioning
confidence: 99%
“…It has been generally accepted that the inhibition of Cox mediates the anti-in ammatory, antipyretic and analgesic effects of NSAIDs (3), where analgesia has been associated with selective Cox-2 inhibition.…”
Section: Introductionmentioning
confidence: 99%